Muscarinic receptor M4 positive allosteric modulators attenuate central effects of cocaine. (1st July 2017) - Dall, Camilla; Weikop, Pia; Dencker, Ditte; Molander, Anna C.; Wörtwein, Gitta; Conn, P. Jeffrey; Fink-Jensen, Anders; Thomsen, Morgane
Highlights: M4 PAMs attenuated the discriminative stimulus and stimulant effects of cocaine. M4 PAM almost abolished cocaine-stimulated dopamine efflux. M4 PAM did not prevent acquisition of cocaine CPP but prevented reinstatement. Previous effects were confirmed with different ligand. Effects were absent in M4 receptor knockout mice. Abstract: Background: Cocaine addiction is a chronic brain disease affecting neurotransmission. Muscarinic cholinergic receptors modulate dopaminergic signaling in the reward system, and muscarinic receptor stimulation can block direct reinforcing effects of cocaine. Here, we tested the hypothesis that specific muscarinic M4 receptor stimulation can attenuate the discriminative stimulus effects and conditioned rewarding effects of cocaine, measures believed to predict the ability of cocaine and cocaine-associated cues to elicit relapse to drug taking. Methods: We tested the M4 -selective positive allosteric modulators VU0152100 and VU0467154 in a drug discrimination assay and a conditioned place preference assay, including extinction and reinstatement of place preference. Specificity of the cocaine discrimination effect was verified using knockout mice lacking either M1 or M4 receptors (M1 −/−, M4 −/− ). We also replicated previous findings in cocaine-induced locomotor hyperactivity and striatal dopamine microdialysis assays. Results: VU0152100 attenuated the discriminative stimulus effect of cocaine in wild-type mice and M1 −/− mice, but not in M4 −/− mice, without affecting rates of responding. As previously shown with VU0152100, VU0467154 almost eliminated cocaine-induced hyperactivity and striatal dopamine efflux. VU0467154 failed to attenuate acquisition of cocaine-conditioned place preference, but facilitated extinction and prevented reinstatement of the conditioned place preference. Conclusions: These findings further support the notion that M4 receptors are promising targets for the treatment of cocaine addiction, by showing that results can be replicated using distinct ligands, and that in addition to blocking reinforcing effects of cocaine relevant to ongoing drug taking, M4 positive allosteric modulators can also attenuate subjective and conditioned effects relevant to relapse.